2012
DOI: 10.3892/or.2012.1783
|View full text |Cite
|
Sign up to set email alerts
|

Demethoxycurcumin inhibits cell proliferation, migration and invasion in prostate cancer cells

Abstract: Abstract. Curcumin (CUR) is a natural agent that has been demonstrated to effectively inhibit prostate cancer growth. However, natural CUR is relatively unstable and can be easily degraded in vivo. Therefore, it is essential to develop other stable curcuminoids. Demethoxycurcumin (DMC) is a candidate that has been verified in several tumor types and has potential for the treatment of prostate cancer. In the present study, we investigated the effects of DMC on proliferation, apoptosis and migration of PC-3 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Meanwhile, an increase in the sub-G 1 peak, which is an characteristic feature of cell apoptosis, was also induced by DMC, suggesting that G 2 /M arrest is an underlying mechanism inhibiting the growth of DMC-treated OSCC cells, which might further turn on an apoptotic program. These results are supported by other published studies which indicate that DMC markedly induced G 2 /M arrest in brain and prostate cancers [24,35]. Evidence in the literature indicates that DMC induced BCL-2-mediated G 2 /M arrest most effectively among CUR, DMC, and BDMC in brain tumors [24].…”
Section: Discussionsupporting
confidence: 86%
“…Meanwhile, an increase in the sub-G 1 peak, which is an characteristic feature of cell apoptosis, was also induced by DMC, suggesting that G 2 /M arrest is an underlying mechanism inhibiting the growth of DMC-treated OSCC cells, which might further turn on an apoptotic program. These results are supported by other published studies which indicate that DMC markedly induced G 2 /M arrest in brain and prostate cancers [24,35]. Evidence in the literature indicates that DMC induced BCL-2-mediated G 2 /M arrest most effectively among CUR, DMC, and BDMC in brain tumors [24].…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, previous studies using cancer cells and N9 microglial cells validated the safety of DMC at 10  μ mol/L [19, 20]. In vivo treatment with DMC had the effect to reduced IL-1 β in the ischemic brain.…”
Section: Discussionmentioning
confidence: 66%
“…DMC, which is a structural analogue of CUR, also exhibits antitumor effects (14) and strongly inhibits proliferation of prostate cancer cells (23). The improved stability of DMC compared to CUR may significantly prolong the time of action of DMC and extend its half-life, suggesting that DMC may be an attractive compound to explore as an anticancer agent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that DMC strongly inhibits proliferation in numerous types of cancer, including prostate cancer, kidney cancer and breast cancer cells (1517). However, the effects of DMC on skin cancer cells remain unknown.…”
Section: Introductionmentioning
confidence: 99%